2012
DOI: 10.1002/hyp.8257
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater–surface water interactions in a lowland watershed: source contribution to stream flow

Abstract: Abstract:The lower coastal plain of the Southeast USA is undergoing rapid urbanisation as a result of population growth. Land use change has been shown to affect watershed hydrology by altering stream flow and, ultimately, impairing water quality and ecologic health. However, because few long-term studies have focused on groundwater-surface water interactions in lowland watersheds, it is difficult to establish what the effect of development might be in the coastal plain region. The objective of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Base cations (BCs) are a semiconservative tracer which has been used to determine if there is a partition of water sources in streams and rivers [ Burns et al ., ; Dunn et al ., ; Soulsby et al ., ]. The BC concentrations are commonly much lower in shallow groundwater compared to deep groundwater as the BC concentration primarily is regulated by water residence time in the subsurface environment [ Garrett et al ., ; Klaminder et al ., ; Wolock et al ., ]. This difference in BC concentration between shallow flow and deep flow paths provides an opportunity to determine the sources of water in mesoscale catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Base cations (BCs) are a semiconservative tracer which has been used to determine if there is a partition of water sources in streams and rivers [ Burns et al ., ; Dunn et al ., ; Soulsby et al ., ]. The BC concentrations are commonly much lower in shallow groundwater compared to deep groundwater as the BC concentration primarily is regulated by water residence time in the subsurface environment [ Garrett et al ., ; Klaminder et al ., ; Wolock et al ., ]. This difference in BC concentration between shallow flow and deep flow paths provides an opportunity to determine the sources of water in mesoscale catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable and sustainable water yield from watersheds in the Southeastern Coastal Plain has become an area of concern in recent years because of changing population growth, land use, and potential climate change. To address this concern, there is a need for a reliable understanding of hydrologic processes and water balance of less disturbed, forested watersheds on low-gradient Coastal Plain (LCP) lands [1][2][3][4][5][6][7]. This reference water balance could be used to quantify the mag-difficulty in accurately estimating the watershed drainage area used in depth-based runoff.…”
Section: Introductionmentioning
confidence: 99%
“…The water table fluctuation (WTF) method is based on monitoring water levels in wells (Rasmussen and Andreasen, ; Coes et al ., ; Delin et al ., ; Lewandowski et al ., ). Two other methods are monitoring soil moisture changes over time (Healy and Cook, ; Nachabe et al ., ) and measuring geochemical indicators and/or environmental isotope concentrations in groundwater and surface water (Genereux, ; Genereux and Jordan, ; Coes et al ., ; Delin et al ., ; Garrett et al ., ). Also, hydrograph separation of storm flow and base flow (Slattery et al ., ; Coes et al ., ; Delin et al ., ; Farahmand et al .…”
Section: Introductionmentioning
confidence: 97%
“…The water table fluctuation (WTF) method is based on monitoring water levels in wells (Rasmussen and Andreasen, 1959;Coes et al, 2007;Delin et al, 2007;Lewandowski et al, 2009). Two other methods are monitoring soil moisture changes over time Nachabe et al, 2005) and measuring geochemical indicators and/or environmental isotope concentrations in groundwater and surface water (Genereux, 2004;Genereux and Jordan, 2006;Coes et al, 2007;Delin et al, 2007;Garrett et al, 2011). Also, hydrograph separation of storm flow and base flow (Slattery et al, 2006;Coes et al, 2007;Delin et al, 2007;Farahmand et al 2007;LaTorre Torres et al, 2011), and heat as a tracer for groundwater flux (Anderson, 2005;Cox et al, 2007;Foulquier et al, 2009) have been shown to provide estimates of groundwater recharge or discharge.…”
Section: Introductionmentioning
confidence: 99%